Effect of external physical vibration lithecbole in obese patients with lower pole stones <15 mm after ESWL: a single-centre, randomized, open label clinical trial - Li, Yunpeng; Lv, Jianlin (Frontiers in Medicine, 2023)
Objective: To investigate the efficacy and safety of external physical vibration lithecbole (EPVL) in obese patients with less than 15 mm lower pole stones following extracorporeal shock wave lithotripsy (ESWL). Methods: 299 obese patients with BMI greater than 30 kg/m 2 and lower pole stones smaller than 15 mm were prospectively randomized into two groups. While ESWL was the only option in the control group, patients in the treatment group accepted EPVL after receiving ESWL. Imaging tests were used to compare the stone expulsion status on day 1 and the stone-free rates (SFR) on the first, second, and fourth weekends. Results: All 299 obese patients were randomly divided into two groups, with 152 patients assigned to the treatment group and 147 assigned to the control group. EPVL was effective in facilitating the expulsion of stone fragments. The treatment group's stone expulsion rate on the first day following EPVL was significantly greater than the control group's (66.4% vs. 51.7%, P=0.009). Stone clearance rates in the treatment and control groups were 63.2% and 55.1% at 1 week (p = 0.041), 84.9% and 70.7% at 2 weeks (p = 0.011), and 90.8% and 79.6% at 4 weeks (p = 0.017), respectively. The complications (hematuria, lumbago, and fever) between the groups did not show any significance (P > 0.05). Patients in the treatment group received an average of 5.2 sessions.EPVL is an efficient and secure procedure that facilitates lower pole stone discharge in obese patients following ESWL treatment. To support the aforementioned conclusions, additional large-scale multi-center prospective studies are required.